Studies on corrosion behavior of a single-crystal superalloy and its sputtered nanocrystalline coatings with solid NaCl deposit in O2 + 38 vol.% H2O environment at 700 °C. (December 2019) - Sun, Wenyao; Wang, Jinlong; Yang, Lanlan; Chen, Minghui; Bao, Zebin; Zheng, Chengyue; Zhu, Shenglong; Wang, Fuhui
Highlights: Media-high temperature corrosion in chloride and water vapor environment is studied. The N5 superalloy shows low corrosion resistance and scale spalls off readily. The two nanocrystalline coatings perform better owing to the formation of alumina. Chlorination and/or oxidation of Ta ruin compactness of the oxide scale. Y inhibits outward diffusion of Ta, improving corrosion resistance of the coating. Abstract: Corrosion behavior of the N5 superalloy (Ni-7.0 Cr-6.2 Al-7.5 Co-5.0 W-1.5 Mo-6.5 Ta-3.0 Re) and two nanocrystalline coatings prepared by magnetron sputtering is investigated in chlorine and water vapor environment at 700 °C. The alloy shows low corrosion resistance. Its oxide scale spalls off readily and includes porous NiO outer layer and NiCr(Al)2 O4 inner one. The nanocrystalline coating performs better. Its oxide scale consists of Al2 O3, NiO and Ta2 O5 . Chlorination and/or oxidation of Ta ruined compactness of scale. The yttrium modified nanocrystalline coating provides the highest corrosion resistance. Its scale is exclusively alumina. Yttrium inhibits the outward diffusion of Ta.